2021
DOI: 10.1177/14614448211031249
|View full text |Cite
|
Sign up to set email alerts
|

Do squeaky wheels get the grease? Understanding when and how municipalities respond to online requests

Abstract: Citizens often attempt to interact with government through online modes of communication such as email and social media. Using an audit study, we examine when and how American municipalities with populations of over 50,000 respond to online requests for information. We develop baselines for municipal responsiveness, including the average rate, time, and quality of responses, and examine whether these response attributes vary based on the mode of communication or the tone of the request. Overall, municipalities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…The way in which a message is perceived by the receiver can significantly influence the response. While Cuillier (2010) or Epstein et al (2021) found that threatening and angry messages, respectively, receive faster responses from public officials than more friendly ones, this research delves deeper and shows that the underlying emotions a request evokes can be associated with responsiveness. Requests that evoke more positive sentiments are more likely not only to receive a response from a public organization in general, but also to receive the information requested.…”
Section: F I G U R Ementioning
confidence: 65%
See 4 more Smart Citations
“…The way in which a message is perceived by the receiver can significantly influence the response. While Cuillier (2010) or Epstein et al (2021) found that threatening and angry messages, respectively, receive faster responses from public officials than more friendly ones, this research delves deeper and shows that the underlying emotions a request evokes can be associated with responsiveness. Requests that evoke more positive sentiments are more likely not only to receive a response from a public organization in general, but also to receive the information requested.…”
Section: F I G U R Ementioning
confidence: 65%
“…In the context of information exchange, researchers have already investigated the important role of emotions and found that a person's mood substantially impacts information sharing (and seeking) behavior (Dardenne et al, 2011;Peters et al, 2009). Applying this idea of reciprocity to the interaction between citizens and government, Epstein et al (2021) describe the customer-related and service-oriented role in which public officials find themselves. In the course of their duty of representing the state and of ensuring a positive service quality evaluation, they are required to manage and control their emotions and expressions to deliver satisfying public services.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations